PERAN PEMASARAN MEDIA ONLINE UNTUK PENINGKATAN PENJUALAN UMKM - Noor, Raden Ajeng Alycia Putri; Juhari, Juhari; Zufriady, Zufriady (LP2M Universitas Bina Bangsa, 2025)
Digital platforms offer significant potential for creating value and enhancing customer engagement, which are crucial for SMEs. However, the adoption of digital marketing by SMEs remains limited, hindering their ability to fully leverage these benefits. This article aims to examine the role of online media marketing in increasing SME sales. A qualitative descriptive approach was employed to conduct this study. A thorough review of relevant literature, including books, papers, magazines, news items, websites, and other scholarly works, was a key step in data collection. The research methodology involved a comprehensive examination of existing literature, with a particular focus on gathering data from sources relevant to the current issue. The information presented here has undergone extensive verification and validation from multiple sources over a significant period. The analysis of various literature reveals that digital marketing is effective in boosting SME sales through platforms such as Instagram, Facebook, and Shopee. It enables SMEs to adopt flexible marketing strategies, reduce costs, and reach wider markets. Despite challenges like limited internet access and technological skill gaps, the benefits far outweigh the costs. This article acknowledges its limitation in not conducting direct research with SME practitioners. Nevertheless, it is expected to contribute to SMEs by encouraging them to utilize online media to enhance visibility, strengthen customer relationships, and achieve significant growth in competitive markets.